We Took the Streets : Fighting for Latino Rights with the Young Lords - Melendez, Miguel (Book collections on Project MUSE., 2005)
An insider's view of the idealism, anger and vitality of the much-maligned group known as the Young Lords as they rose to become the most respected and powerful voice of Latin American empowerment in the US. From their emergence in the 60's to their fracture in 1972, this is the story of how one group took on the establishment - and won.